Data Augmentation using Generative-AI - Gowda, Samarth R; C., Pavithra H; R., Sunitha; M., Somaiah K; H., Suraj S; Rao, Yashas R (Journal of Innovative Image Processing, 2024)
This study presents an approachable tool for data augmentation that makes use of artificial intelligence (AI). It can handle text and visual data, assisting customers in optimizing their data collecting for a range of applications. The system breaks down CSV documents providing insights using libraries such as transformers, which are used in the field of Natural Language Processing (NLP). It assesses the insights in addition to applying data augmentation techniques like word control and equivalent substitution. This method improves the text data by quickly balancing the final dataset. This study uses Generative III-disposed Organizations (GANs) to handle the images. Users can change settings like rotation, scale, and translation for a variety of high-quality images. This use case goes beyond simple growth and touches on the territory of artificial intelligence. With an emphasis on usability, the User Interface (UI) enables researchers to customize the processes according to their specific datasets.